Students’ perceptions toward vocational education on online learning during the COVID-19 pandemic - Khusni Syauqi; Sudji Munadi; Mochamad Bruri Triyono (International Journal of Evaluation and Research in Education (IJERE), 2020)
The impact of the Covid-19 pandemic has spread almost throughout the world. It makes all educational institutions in Indonesia experienced a lockdown in an undetermined time. As a result, teachers must switch to online teaching methods, while students must adapt to the online learning environment in a short time. Vocational education emphasizes not only the mastery of knowledge but also skills. In the learning process, students' perceptions can be used as evaluations to improve the quality of learning. This study aimed to provide an overview of students' perceptions of Mechanical Engineering Education on online learning as a result of the impact of the Covid-19 pandemic. This study used survey methods and data collection in the form of instruments with a Likert scale with a sample of 56 students. The results of this study indicate that teachers in managing online learning are not in line with student expectations. Students feel that online learning has not provided better experience and productivity in mastering competencies, but can provide motivation and ease in their learning. Some students stated that they had the ease of access to resources, but students were still reluctant to use it sustainably in the future.